Allostatic Load in Perimenopausal Women With Migraine - Alebna, Pamela; Maleki, Nasim (Frontiers in Neurology, 2021)
Objective: There is very limited data on women with migraine disease as they age and transition to menopause. Despite evidence for the increased burden of the disease during this transition, there is no data on the association between migraine and allostatic load as a marker of cumulative biological risk. We aimed to determine whether women with migraine suffer from higher levels of allostatic load during perimenopausal transition. Methods: A total of 2,105 perimenopausal women from the first wave of the Study of Women's Health Across the Nation (SWAN) were included in this study. Allostatic Load (AL) score was estimated for each participant from the measurements of: systolic and diastolic blood pressure, C-reactive protein level, high-density lipoprotein cholesterol level, total cholesterol level, waist-to-hip ratio, fasting serum glucose, triglycerides, and dehydroepiandrosterone levels. Results: Of the 2,105 participants included in the study, there were 369 migraineurs and 1,730 controls. Migraineurs had 63% higher odds of increased load score (odds ratio 1.63; 95% confidence interval, 1.17–2.29). Compared to controls, migraineurs were more likely to experience sleep problems in the univariate analysis, however despite the high burden of sleep problems, there were no significant associations between allostatic load and sleep disturbances in perimenopausal women with migraine after controlling for other factors. Conclusion: This is the first study to systematically and quantitatively examine allostatic load in migraine patients. The findings establish that migraineurs are more likely to experience higher allostatic load than their non-migraine counterparts during perimenopausal transition. The findings encourage new lines of investigation for lowering the burden of the disease through interventions that modify the levels of allostatic load biomarkers examined in this study.